Vulnerabilities of Highly Skilled Immigrants in Canada and the United States. - Somerville, Kara; Walsworth, Scott (American Review of Canadian Studies, 2009)
Despite similar permanent status immigration categories (Economic, Family, and Refugee), the experiences of skilled immigrants in Canada and the United States are quite different. The point system used to select applicants for the Economic Class in Canada makes skilled immigrants vulnerable to a number of perils after the migrant lands. Foreign credentials and work experience are discounted by Canadian employers, who also impose a discriminatory income penalty on minorities. While previous cohorts of Economic Class migrants may have been warned of these perils via reliable migrant networks, new Canadian research suggests that recent cohorts have no such safety net. This article examines the economic integration experiences of Economic Class migrants in the United States in light of the Canadian experiences. The vulnerabilities reported in Canada do not appear to be transferable to the United States, because immigration policy in the US stresses pre-landing employment commitments via employer sponsorship. Accordingly, prospective Economic Class migrants to the United States do not migrate without first knowing how their credentials and “minority status” will affect employment opportunities. However, for the 85,000 skilled workers admitted to the United States on H-1B temporary visas each year, the perils noted in the Canadian experience are relevant, as are a number of additional concerns.